Unitáriusok egyetemjárása a 16. és 17. században – Narratívák és a Bessenyei-probléma - Lovas, Borbála (Gerundium, 2017)
Unitarian Peregrination in the 16th and 17th century: Narratives and the Bessenyei-problem. This paper provides a fresh examination of the peregrination of Transylvanian Unitarian students in the 16 th and 17th century. Focusing on keyexamples, putting the details into a more accurate context, the question of the choice of university – Wittenberg, Frankfurt, Padua, Rome, Vienna, or Dutch universities – among different generations becomes more nuanced. Bookentries, inscriptions, marginalia, letters, diaries, and travelentries are used to identify new names in the matriculas, and to refine knowledge of student networks: social circles (and patrons), contacts, and relations. This study examines members of the Kornis and Haller families, and provides a clearer identification of two Wittenberg students: Jakab Bessenyei and Péter Bessenyei.